ANALYSIS OF CHILDREN’S EXPRESSIVE SPEECH ACTS IN SAYOUNARA BOKUTACHI NO YOUCHIEN MOVIE: ANALISIS TINDAK TUTUR EKSPRESIF ANAK DALAM FILM SAYOUNARA BOKUTACHI NO YOUCHIEN - Yuniarsih Yuniarsih; Eky Kusuma Hapsari; Sekar Adinda Reviona (Jurnal Kata, 2022)
This study aims to determine the types of speech acts and forms of expressive speech of children. The background for this research is moral education or doutoku kyouiku (道徳教育) which has been taught from an early age to children, making them unable to express expressions straightforwardly. The theory used in this study is the theory of Searle (1969) and Wijana (1996) as a reference regarding the types and forms of expressive speech acts. The results obtained from the analysis are the types of direct literal speech acts that are mostly used by children. Based on the analysis of 24 data, it is known that there are expressions of gratitude (1), worry (2), anger (3), apologize (3), praise (3), criticize (5), blaming (1), feeling guilty (1), sad (2), happy (2), fear (1). As well as indicators of nonverbal language contained in this study as many as 10 data.